A CORRELATIONAL STUDY BETWEEN STUDENTS’ VOCABULARY MASTERY AND WRITING DESCRIPTIVE TEXT ABILITY - Sri Lestari; Luqman Al Hakim (English Education Department Slamet Riyadi University Surakarta, 2023)
The objective of this study was to determine the correlation between students' vocabulary mastery and descriptive writing ability of 8th grade students at SMPN 18 Surakarta in the academic year 2022/2023. This study is a quantitative study using correlation design. The research sample was 31 grade 8 students selected by cluster random sampling method. The tools used in the study were a vocabulary test and a writing test. This is proven through the results after analyzing two variables using the Person Product Moment formula, with the results rxy 0.685 > rtable at the significance level of 0.05 = 0.355 and both 0.001 = 0.479. This means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is a positive correlation between students' vocabulary mastery and descriptive writing ability. Keywords: Correlational, Vocabulary Mastery, Writing Ability, Descriptive Text.